Advances in Electrolytic Manganese Residue: Harmless Treatment and Comprehensive Utilization - Weijian Yu; Xiaoya Li; Wenting Xu; Qingjun Guan; Fujia Zhou; Jiani Zhang; Li Wang; Yanxiu Wang; Honghu Tang (Separations)
Electrolytic manganese residue (EMR) is a byproduct of electrolytic manganese production, rich in soluble pollutants such as manganese and ammonia nitrogen. Traditional stockpiling methods result in contaminant leaching and water pollution, threatening ecosystems. Meanwhile, EMR has significant resource-recovery potential. This paper systematically reviews the harmless process and resource technology of EMR, efficiency bottlenecks, and the current status of industrial applications. The mechanisms of chemical leaching, precipitation, solidification, roasting, electrochemistry, and microorganisms were analyzed. Among these, electrochemical purification stands out for its efficiency and environmental benefits, positioning it as a promising option for broad industrial use. The mechanisms of chemical leaching, precipitation, solidification, roasting, electrochemistry, and microorganisms were analyzed, revealing the complementarity between building materials and chemical materials (microcrystalline glass) in scale and high-value-added production. But the lack of impurity separation accuracy and market standards restricts its promotion. Finally, it proposes future directions for EMR resource utilization based on practical and economic considerations.